Emerging and Disease-Specific Mechanisms of Hepatic Stellate Cell Activation - Wallace, Michael C.; Friedman, Scott L.; Mann, Derek A. (Seminars in Liver Disease, 2015)
The last decade has seen a rapid expansion in our understanding of the mechanisms leading to hepatic stellate cell activation. The classic activation pathway of initiation, perpetuation and regression remains as a useful model; however, the emergence of several new pathways and mediators has revealed a deeper complexity than previously appreciated. Although core fibrogenic pathways exist across organs and disease types, there is accumulating evidence for disease- and context-specific mechanisms that may modulate or drive hepatic fibrogenesis. Hence, a “one size fits all” approach to antifibrotic therapy may not be appropriate for all disease settings. The authors present a focused and concise update of the most recent advances in our understanding of hepatic stellate cell activation pathways, while highlighting several challenges that may be constraining progress. This summary provides a foundation to further expand our knowledge of this unique cell type and its contributions to human liver disease.
Keywords: hepatic stellate cell; hepatic fibrosis; antifibrotic therapies; nonalcoholic fatty liver disease; chronic viral hepatitis